Sustainable structural design optimisation of steel truss - Wicaksana, Enrian (Nanyang Technological University, 2024)
The built environment industry produces tremendous amount of carbon emission. In 2019, buildings accounted for 39% of global carbon emissions, 11% of which was in form of embodied carbon which generated from the materials, construction, and the end-of-life phases (World Green Building Council, 2019). In Singapore, buildings contributed to 20% of the total carbon emission (Singapore Green Building Council & Building and Construction Authority, 2022). However, studies indicated that it was possible to reduce the embodied carbon of the building structures by correctly design the structure (Kaethner & Burridge, 2012). This final year project focuses on developing workflow to optimize steel trusses using parametric modelling. Pedestrian steel bridge with pratt truss structural system is used as case studies in this project. The proposed workflow emphasizes on the use of automated iteration by changing the variables such as the height of the bridge and the subdivision or the number of panels. The program is developed using Visual Basic for Application (VBA) with ETABS Application Programming Interface (API) to link between Excel and ETABS as the analysis and design software. In this project, a total of 11313 iterations were carried out using the program. The results are then used derive design guideline to determine the truss height and the bracings spacing to obtain optimum solution. The study finds that span2/height ratio turns out to be an important parameter although it is not as commonly used as span/height ratio. The span2/height shows strong linear relationship with the span length within the range 18 to 36m. The design guideline, derived empirically and the assumption that the bracing angle is related to the section type, shown to result in a close approximation that deviates from the optimum solution’s weight within less than 3% in average. The author believes that the method and findings can be used for broader use on different structural systems to obtain a more sustainable solutions on the design phase of structures.